Ecosystem health assessment: a PSR analysis combining AHP and EW methods for Sansha Bay, China - Li, Yue; Huang, Yaling; Zhang, Xiaoyun; Jiang, Yawen; Jing, Xiaoshan; Deng, Yihong; Li, Rongmao; Jiang, Degang; Mu, Jingli (Frontiers in Marine Science, 2024)
Maintaining the health of coastal aquaculture ecosystems is crucial for sustainable development.Therefore, establishing a specific ecosystem health assessment index system for aquaculture bays is paramount. This system allows for the evaluation of the health status of these bays and aids in the planning and restoration of fishery habitats. Utilizing the well-known "Pressure-State-Response" framework, a comprehensive evaluation index system with 14 indicators was developed. Additionally, the analytic hierarchy process and entropy weight methods were employed to assess the ecosystem health of Sansha Bay, a representative aquaculture bay in Fujian Province, China. The results revealed variations in health status across four zones in 2020, categorized as "good" or "excellent". However, the security index was more spatially distributed and classified from "fair" to "safety". Key indicators critical to sustaining the health of the aquaculture bay ecosystem included the regional environmental risk index, the proportion of industrial discharge outlets, the zooplankton species diversity index, the phytoplankton species diversity index, the molar ratio of phosphorus to nitrogen, and the size of nature reserves. According to the assessments of ecosystem health and ecological security, vigorous endeavors in aquatic ecology are paramount to ensure the enduring sustainability of aquaculture, with a specific emphasis on Zoning 1 and Zoning 4. These findings not only enhance and expand the methods for assessing the health of aquaculture bay ecosystems but also provide a scientific basis for the conservation of fishery habitats and the green, high-quality development of the aquaculture industry in